Sex, Drugs, and Country Music? A Content Analysis of Substance use, Sex, Violence, and Weapons in Country Music (Global Journal of Human-Social Science, 2014)
Because adolescents are strongly influenced by years listen to an average of 3 hours of music per day, and 98 million US country music, we aim to describe the music.
Keywords: country music; music; mass media; adolescents; sexual activity; alcohol use; tobacco; weapons; violence